From Manga Bible to Messiah: A Pop-culture Exploration of the Indonesian Christian Comics - Hendrikus Paulus Kaunang; Leonard Chrysostomos Epafras (International Journal of Interreligious and Intercultural Studies, 2021)
Comics culture has a long precedence in Indonesian art tradition. Earlier visual art appeared in the Hindu-Buddhist temples and in the colonial period. Once, Indonesian comics enjoyed the golden age in the 1970s and 1980s in which the comics sought inspiration from local legends and wayang themes. However, the flood of Western and Japanese comics eroded the supremacy of Indonesian comics. For the latter, it is part of the Japanophile, which later followed by Koreaphile as two global cultural forces overwhelmed Indonesia presently. Manga comics, for example, has become a dominant visual art in the comics market in Indonesia and influencing the style of Indonesian visual art production. Religion is another socio-cultural terrain affected by this cultural development. The present article is an exploration of the comics as a visual art in the religious landscape of Indonesia, especially among the Christians. Comics as the locus of the technology of enchantment renders the trace of religious shift among the average religionists. Employing visual rhetoric criticism, the article will look at the ideological and rhetorical elements of the visual production, and the cultural shifting in the Indonesian Christianity. It further touches upon the notion of cuteness (chibi) and gender as examples of religious rhetoric maintaining a certain ideological position.